TRIPS BY WORLDS - Яремійчук, Р. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Material contains flashbacks and reflections of author about the oversea trips by the countries of Europe, Asia, America.